ECO-INNOVATION AND SUSTAINABILITY IN HOSPITALITY: CULTURAL AND ENVIRONMENTAL STRATEGIES IN THE GASTRONOMY OF PARÁ. (REMUNOM, 2025)
This theoretical essay analyzes eco-innovation in the hospitality sector, with an emphasis on Pará cuisine as a strategy for incorporating sustainable practices and promoting socio-environmental development in the Amazon region. Drawing on an interdisciplinary approach and a conceptual analysis grounded in the literature on sustainability, circular economy, and environmental innovation, the study examines how eco-innovation can link the preservation of natural resources with the cultural and economic valorization of the region. Pará cuisine, characterized by the use of native ingredients and well-established culinary traditions, is understood as a strategic driver for strengthening sustainable tourism and responsible hospitality. The essay discusses the integration of environmental, social, and economic dimensions into organizational practices, highlighting the role of local supply chains, efficient resource management, and innovation in production processes. Furthermore, theoretical gaps in the application of eco-innovation to the hospitality context are identified, leading to the proposal of an integrative model that connects cultural, organizational, and technological factors. It is concluded that the systemic adoption of eco-innovation in Pará gastronomy contributes to reducing environmental impacts, strengthening cultural identity, and generating sustainable economic value, positioning it as a strategic instrument for building a more resilient hospitality sector aligned with Amazonian specificities.